Structural Analysis and Mutant Growth Properties Reveal Distinctive Enzymatic and Cellular Roles for the Three Major L-Alanine Transaminases of Escherichia coli - Peña-Soler, Esther; Fernandez, Francisco J.; López-Estepa, Miguel; Garces, Fernando; Richardson, Andrew J.; Quintana, Juan F.; Rudd, Kenneth E.; Coll, Miquel; Vega, M. Cristina (PLOS ONE, 2014)
In order to maintain proper cellular function, the metabolism of the bacterial microbiota presents several mechanisms oriented to keep a correctly balanced amino acid pool. Central components of these mechanisms are enzymes with alanine transaminase activity, pyridoxal 5′-phosphate-dependent enzymes that interconvert alanine and pyruvate, thereby allowing the precise control of alanine and glutamate concentrations, two of the most abundant amino acids in the cellular amino acid pool. Here we report the 2.11-Å crystal structure of full-length AlaA from the model organism Escherichia coli, a major bacterial alanine aminotransferase, and compare its overall structure and active site composition with detailed atomic models of two other bacterial enzymes capable of catalyzing this reaction in vivo, AlaC and valine-pyruvate aminotransferase (AvtA). Apart from a narrow entry channel to the active site, a feature of this new crystal structure is the role of an active site loop that closes in upon binding of substrate-mimicking molecules, and which has only been previously reported in a plant enzyme. Comparison of the available structures indicates that beyond superficial differences, alanine aminotransferases of diverse phylogenetic origins share a universal reaction mechanism that depends on an array of highly conserved amino acid residues and is similarly regulated by various unrelated motifs. Despite this unifying mechanism and regulation, growth competition experiments demonstrate that AlaA, AlaC and AvtA are not freely exchangeable in vivo, suggesting that their functional repertoire is not completely redundant thus providing an explanation for their independent evolutionary conservation.